Trusted computing - Mitchell, Chris (Institution of Engineering and Technology, 2005)
This book is designed to provide an introduction to trusted computing technology and its applications. It is divided into four main parts, as follows: 1. Introduction to trusted computing; 2. Trusted computing technologies; 3. Applications of trusted computing; and 4. The future of trusted computing. The first part consists of three chapters, each approaching trusted computing from a somewhat different perspective. In the second part, made up of Chapters 4 and 5, two technologies fundamental to the future application of trusted computing are discussed. The discussion of applications of trusted computing in Part 3 contains five chapters, each looking at a different possible application of this technology. Finally, Part 4 contains a single chapter giving thoughts on the future of this potentially revolutionary technology.